Peningkatan Pengetahuan Ibu Hamil tentang Pentingnya Antenatal Care (ANC) - Rosmiati Rosmiati; Susi Rabuana; Norma Safitri (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2026)
Antenatal Care (ANC) is a health service provided to pregnant women on a regular and planned basis to monitor the health of the mother and fetus. However, some pregnant women still do not utilize ANC services optimally due to a lack of knowledge and understanding. This community service activity aims to improve pregnant women's knowledge of the importance of ANC through health education. Implementation methods include counseling, interactive discussions, and knowledge evaluation. The results of the activity indicate an increase in pregnant women's knowledge regarding the definition, purpose, benefits, and schedule of ANC visits. This activity is expected to increase pregnant women's compliance with regular ANC visits, thereby supporting efforts to prevent pregnancy complications.